Evaluation of School Fund Management as a Post Conflict Education Recovery Strategy in Dili City, Timor Leste - Yus Tya Wiranti; Emiliana Sri Pudjiarti (International Journal of Studies in International Education, 2026)
This research is motivated by the importance of school fund management as a post-conflict education recovery strategy in Dili City, particularly at SMP Akadiru-hun, which faces challenges such as damaged facilities, limited teacher capacity, and weak financial governance. A literature review indicates that Post-Conflict Education Theory and Educational Financial Management Theory emphasize efficiency, priority, transparency, and accountability as the foundation for education system recovery. This study used a mixed methods approach, with quantitative data collected in the form of questionnaires from 20 respondents and qualitative data collected through in-depth interviews with four key informants. The descriptive statistical analysis showed an average score of 17.85 for the Education System Recovery and Strengthening Index. Efficiency and Priority of Fund Use was 17.45, and Transparency and Accountability of Fund Management was 18.75. Pearson correlation analysis showed a moderate positive relationship between Education System Recovery and Strengthening and Transparency and Accountability in Fund Management (r = 0.360). In contrast, the relationships between Education System Recovery and Strengthening and Efficiency and Priority of Fund Use (r = -0.014) and Efficiency and Priority of Fund Use and Transparency and Accountability in Fund Management (r = 0.056) were very weak and insignificant. Qualitative findings confirm that school fund management that follows government standard operating procedures contributes to post-conflict education recovery, although internal transparency still needs improvement. This study concludes that efficient, targeted, and accountable school fund management can be an effective strategy in post-conflict education recovery.